Konsep Pendidikan Islam Perspektif HOS Tjokroaminoto - Mustofa Kamil, Alfian Nur (?ALI?A, 2018)
This research is motivated by the fact that there are stillmany young people who still do not know the thought of HOSTjokroaminoto in the field of Islamic education. Most people think thatHOS Cokroaminoto is better known as a great agitator and politician, hasno concept of Islamic education. Even more concerning again the younggeneration is now especially junior high school students who do not knowthe names of national heroes of Indonesia's movement. Meanwhile, somepeople also tend to think that HOS Cokroaminoto is only a political partyfigure, when he is a national hero who has been instrumental in laying thefoundations on various national issues. But until now his capacity as anextraordinary figure is lacking the national spotlight. The youngergeneration recognizes the street name of HOS Cokroaminoto, the schoolname of Cokroaminoto but does not understand who exactly is HOSCokroaminoto and how the footsteps of his struggle.From this research can be described that education and teachingdesired by HOS Tjokroaminoto is, to form a true and virtuous anddemocratic Muslim man, competent and responsible for the welfare of Nusaand Bangsanya, so it becomes a source of mercy for the whole of nature.And in azaz program and tandhim program of Syarikat Islam mentionedthat the matter of education should not be the nature and the despair ofhumankind. Education initiated by HOS Tjokroaminoto also should notseparate general science and religion. This is conceived by the intention toform an academic and religious human who has the spirit of Islam, freespiritedand democratic and broad-minded and insightful love of thehomeland. The principle of education is the feeling of nationalism ofnationalism must remain preferred in terms of studying various types ofknowledge. Not to happen after studying the various sciences, we are morewest of the westerners themselves or more than the Arabs themselves.